Кріоабляція аденогіпофіза в лікуванні хронічного больового синдрому у хворих на злоякісні новоутворення IV стадії - Циганков, О.В.; Чиж, М.О.; Гладких, Ф.В. (Ukrainian Journal of Radiology and Oncology, 31(3), 303-314., 2023)
The data of the European Society For Medical Oncology (ESMO) indicate that 64.0% of cancer patients with the fourth stage of cancer have chronic pain syndrome, which is the main factor that significantly affects the quality of life. In 46.0% of patients, it is not possible to obtain a stable analgesic effect with modern methods of analgesia, including interventional methods and pharmacotherapy. Refractory oncological pain stimulates the search for new methods of pain relief. Purpose – retrospective assessment of the effectiveness of the selective stereo- tactic transnasal transsphenoidal cryoablation of the adenohypophysis in the treatment of chronic pain syndrome in patients with stage IV malignant neoplasms. Materials and methods. 45 microsurgeries were performed – stereotactic selective transnasal transsphenoidal cryoablation of the adenohypophysis with endoscopy. Over the period from 2014 to 2018, 45 patients with stage IV malignant hormone- dependent neoplasms of various somatic organs and chronic pain syndrome underwent microsurgery. Results. The analgesic effect appeared 4–6 hours after the microsurgery. In 95.6% of patients, an analgesic effect was achieved to a greater extent (according to the numeric rating scale (NRS) for pain, its intensity decreased from 7–9 points to 1–3 points); in other patients, the analgesic effect was achieved to a lesser extent (according to the NRS, pain intensity decreased from 7–9 points to 3–5 points), regardless of the condition and age of the patient. Accordingly, the dosage was reduced or opioid analgesics were discontinued. Severe complications after the cryoablation of adenohypophysis, such as meningitis, diabetes insipidus, and hypopituitary syndrome were not observed. In the postoperative period, three patients were treated for mild hypopituitary syndrome, and two patients were treated for liquorrhea with conservative therapy for 3–5 days. Conclusions. Stereotactic selective transnasal transsphenoidal cryoablation of the adenohypophysis is an effective microsurgery in the treatment of chronic pain syndrome in stage IV cancer patients. It improves the patient’s condition and quality of life. The analgesic effect appears in the first hours after surgery. Due to the use of cryoprobes with a diameter of 1.2 mm and 1.8 mm, the surgery is minimally traumatic and can be performed on patients in critical condition.
Cryoablation of the adenohypophysis in the treatment of chronic pain syndrome in patients with stage IV malignant neoplasms
Tsyhankov, O., Chyzh, M., & Hladkykh, F. (2023). Cryoablation of the adenohypophysis in the treatment of chronic pain syndrome in patients with stage IV malignant neoplasms. Ukrainian Journal of Radiology and Oncology, 31(3), 303-314. https://doi.org/10.46879/ukroj.3.2023.303-314
Keywords: stereotactic selective transnasal trans-sphenoidal cryoablation of the adenohypophysis with endoscopy; chronic pain syndrome